2016
DOI: 10.1080/00016357.2016.1235227
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the use of cone-beam computed tomography and panoramic radiography in the assessment of pre-eruptive intracoronal resorption

Abstract: CBCT detected more cases of PIR than panoramic radiography. The mandibular third permanent molar was the most commonly affected tooth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 15 publications
6
42
3
5
Order By: Relevance
“…Tooth prevalence in the present study (0.32%) was lower than that in all previous studies (0.5%‐3.47%) (Table ) . The majority of prevalence studies reported tooth prevalence of less than 1% . This low prevalence could imply that panoramic radiographs should not be prescribed to screen for PEIR, but rather, all panoramic radiographs should be routinely screened for PEIR.…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…Tooth prevalence in the present study (0.32%) was lower than that in all previous studies (0.5%‐3.47%) (Table ) . The majority of prevalence studies reported tooth prevalence of less than 1% . This low prevalence could imply that panoramic radiographs should not be prescribed to screen for PEIR, but rather, all panoramic radiographs should be routinely screened for PEIR.…”
Section: Discussioncontrasting
confidence: 77%
“…The lack of a significant difference in PEIR prevalence between the sexes also corresponded to the prevalence in previous studies . The highest patient prevalence in a previous study was in a Malaysian population (27.3%), whereas most other studies reported patient prevalence to be lower than 10% (0.85%‐8.1%) (Table ) . The different prevalences between studies could be due to differences in ethnicity, the types of teeth examined, or the age range of the population (Table ).…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations